Adenovirus Methods and Protocols Volume 1: Adenoviruses, Ad Vectors, Quantitation, and Animal Models - Wold, William S. M.; Wold, William S. M.; Tollefson, Ann E.; Tollefson, Ann E. (Methods in Molecular Medicine, 2007)
Adenovirus Methods and Protocols, Second Edition, now in two volumes, is an essential resource for adenovirus (Ad) researchers beginning in the field, and an inspirational starting point for researchers looking to branch into new areas of Ad study. In addition to updating and expanding important chapters from the first edition, the authors have added new chapters that address innovative, exciting areas of emphasis in Ad research, including Ad vector construction and use, real-time PCR, use of new animal models, and methods for quantification of Ad virus or virus expression/interactions. Each of the protocols presented in these volumes is written by trendsetting researchers in their respective areas of expertise. Volume 1 addresses several important techniques for construction of adenoviruses for use as vectors and for basic research. Highlighted topics include deletion mutants, capsid modifications, insertions, and gene replacements in human, murine, bovine, and ovine adenoviruses. In Volume 2, the authors focus on methods that elucidate and quantitate the interactions of Ad with the host. Each of the protocols in these volumes provides a general introduction, followed by tried-and-true step-by-step methods. Both novice and experienced researchers will reap tremendous benefit from these groundbreaking volumes in Ad research.